BERTAHAN DAN KEBERLANJUTAN PT. INDOFOOD SUKSES MAKMUR TBK MELALUI ANALISIS RASIO PROFITABILITAS: ANALISIS RASIO PROFITABILITAS - Octa, Octavia Azizun M.P; Melita Ika; Ety Meikhati (Jurnal Bisnis Manajemen dan Akuntansi (BISMAK), 2024)
This research was conducted to evaluate how a company has the ability to survive the Covid-19 pandemic and be sustainable through profitability ratio analysis. The object of this research is PT. Indofood Sukses Makmur Tbk. The data used in this research is secondary, namely in the form of an Annual Report taken from the Indofood CBP company website. The research results show that based on the profitability ratio analysis using GPM it is above the industry standard of 1.6%, meaning that the company's operational condition is in good condition. Based on the results of calculating the NPM, ROI and ROE ratios, it was concluded that the company was in poor condition because it was still below industry standards.